Estimation of Initial Functions for System with Delays Based on Adjoint Sensitivity Analysis. (2016) - Fujarewicz, Krzysztof
Abstract: The work presents a gradient-based approach to estimation of initial functions of time delay elements appearing in models of dynamical systems. It is shown how to generate a gradient of the estimation quality index in the initial function space using adjoint sensitivity analysis. Results of gradient-based estimation of the initial function for exemplary model are presented.